Analysis of Line to Ground Fault in Inverter FED IM Drive System - Negi, Bhawana; Sharma, Vivek; Kholia, Pooja (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*264.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942705);" role="presentation">Inverter configuration is presented for the Induction Motor drive. One inverter is design for the step-down voltage <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*277.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924663);" role="presentation">and the second inverter is designed for the step-up voltage. PWM use to provide the gate signal to the MOSFET in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*290.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895689);" role="presentation">the circuit. The inverter and the induction motor used as industrial appliances, so it is important to monitor and analyse <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903817);" role="presentation">the fault of the inverter output. While doing the conversion of ac to dc and dc to ac using the power electronics device <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936822);" role="presentation">the harmonics exist. Due to the malfunction in the VSI and CSI the faults are introduced. The current waveform is <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900295);" role="presentation">taken from each phase and the spectrum is analysed. The harmonic analysis with the help of FFT transform is carried <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928559);" role="presentation">out for the short circuit as well as normal condition. The simulation of the VSI and CSI using MATLAB is compared <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936457);" role="presentation">for both conditions i.e. without fault and line to ground circuit faults.